Yielding Returns on Homeless Policy Through the Micro‐Economisation of Housing First Recipients. (12th May 2021) - Grainger, Garrett L.
Abstract : Housing First is a hegemonic model of homeless services that advocates immediate placement in permanent supportive housing without preconditions such as sobriety, treatment, or employment. Federal authorities in the United States have adopted Housing First as a governmentality to make social investments through homeless policy. Although research has examined logics that federal authorities used to make this social investment, sociologists have devoted little attention to techniques that frontline workers use to yield returns on social investment in neoliberal cities. This knowledge gap hinders sociologists from theorizing contemporary urban poverty governance. I make three contributions that address this shortcoming. First, I present a unique qualitative analysis that examines techniques that Housing First providers in a U.S. Rust Belt county use to select a lease configuration for their clients. Second, I expand the definition of economization to incorporate logics that Housing First providers use to estimate transaction costs they will confront while mediating rental market exchanges with a particular lease configuration. Third, I demonstrate, unlike federal policymakers who economize homeless populations as public expenditures to make social investments, service providers economize homeless individuals as transaction costs to yield returns on Housing First in urban communities.